2017
DOI: 10.1177/0956797617693004
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ideological Prejudice

Abstract: A major shortcoming of current models of ideological prejudice is that although they can anticipate the direction of the association between participants’ ideology and their prejudice against a range of target groups, they cannot predict the size of this association. I developed and tested models that can make specific size predictions for this association. A quantitative model that used the perceived ideology of the target group as the primary predictor of the ideology-prejudice relationship was developed wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 37 publications
(51 reference statements)
14
104
1
Order By: Relevance
“…Our dependent variables were attitudes toward the target person as assessed on a feeling thermometer (e.g., Brandt, 2017). For this measure, participants rated their feelings toward the target person on a 10point scale, ranging from 0°to 100°.…”
Section: Methodsmentioning
confidence: 99%
“…Our dependent variables were attitudes toward the target person as assessed on a feeling thermometer (e.g., Brandt, 2017). For this measure, participants rated their feelings toward the target person on a 10point scale, ranging from 0°to 100°.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, by manipulating the ideological salience of scientific findings, found that liberal and conservative partisans interpret scientific findings in a symmetric way, with these judgments being driven by perceptions about the ideological stances of research teams, and the potential for political use of scientific findings (see also Nisbet, Cooper, & Garrett, 2015). This conclusion is consistent with Brandt's (2017) work about the roots of ideological prejudice (see also Brandt & Crawford, 2019;Crawford et al, 2014; , as well as prior theorizing about the psychological basis of science denial among conservatives (Gauchat, 2012;Mooney, 2005).…”
Section: Political Partisans As Symmetricmentioning
confidence: 56%
“…Despite the clear temperamental, cognitive, and personality differences between political liberals and conservatives at the trait level (Jost, 2017a;Jost et al, 2003), there appears to be a substantial degree of symmetry in partisans' behavioral and/or situational interactions with political stimuli across the ideological spectrum (for a brief review, see Clark & Winegard, 2020). For example, Brandt (2017) reported an analysis that showed how both liberals and conservatives express prejudice (operationalized using feeling thermometers in relation to positivity and/or negativity toward different groups) against a range of targets who are popularly linked with the opposite side of the ideological spectrum. For example, American liberals expressed warmth (i.e., liking) toward groups such as homosexuals, transgendered people, and Democrats, while disliking Christians and Republicans.…”
Section: Political Partisans As Symmetricmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, this seems consistent with the shifting focus from old‐fashioned to modern forms of prejudice (Dovidio, Gaertner, & Pearson, ). Indeed, the influence of politics in prejudice research has been cited in work on ideological conflict (Brandt, ), concept creep (Haslam, ), and politics and science (Duarte et al ., ). From this view, there is no need to consider emergent social identities.…”
Section: Possible Alternative Explanationsmentioning
confidence: 97%